Sugarcane Ripeners in Florida - Dennis C. Odero; Curtis R. Rainbolt; Robert A. Gilbert; Joan A. Dusky (EDIS)
Ripeners can be incorporated as an important component of sugarcane production management strategy. This revised 2-page fact sheet was written by D. C. Odero, C. R. Rainbolt, R. A. Gilbert, and J. A. Dusky, and published by the UF Department of Agronomy, October 2011. Photo by ruumo/CC BY-SA 2.0